Quality of Service and Accessibility of Health Services and Its Implications for Patient Compliance through Patient Satisfaction as an Intervening Variable at the Medical Rehabilitation Polyclinic of Meranti Islands Regency Hospital - Ravi Sanjani; Abdul Gani Sidqi; Vip Paramarta; Chevie Wirawan; Ayu Laili Rahmiyati (LP2M IAIN Palopo, 2026)
Service quality refers to the extent to which healthcare services can improve the desired health outcomes in accordance with the abilities and knowledge of professionals. One of the services in hospitals is Medical Rehabilitation. Based on the visit data to RSUD Kabupaten Kepulauan Meranti in 2024 at the Medical Rehabilitation Polyclinic, the three most common diseases out of the top ten at the Rehabilitation Polyclinic were obtained, namely: Sequela of cerebral infarction, primary gonarthrosis, and Low Back Pain. Currently, RSUD Kab. Kep. Meranti has only one Medical Rehabilitation Specialist Doctor who practices from Monday to Wednesday. This study is a quantitative research with an associative approach aimed at determining the effect of service quality and service accessibility on patient satisfaction and compliance with a total of 90 respondents. Based on the results of data analysis and hypothesis testing conducted simultaneously, Service Quality, Service Accessibility, and Patient Satisfaction have a significant effect on Patient Compliance. Nevertheless, the coefficient of determination (R²) value of 0.257 indicates that the regression model can only explain 25.7% of the Patient Compliance variable, while the remaining 74.3% is influenced by other factors not studied in this research.